2022
DOI: 10.20471/acc.2022.61.02.02
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomical and Measurement Study of Rosenmüller Fossa and Oropharyngeal Structures Using Cone Beam Computed Tomography

Abstract: SUMMARY The objective of this study was to assess Rosenmüller fossa (RF) anatomy and neighboring structures using cone beam computed tomography (CBCT). A total of 1000 patients were analyzed using CBCT. The reference points were based on the spina nasalis posterior (Snp) and basion. The length between RF and neighboring structures were measured.The mean distance from Snp to the posterior pharyngeal wall was 17.7 mm. The mean distance from right to left torus levatorius was 25.69 mm. The mean depth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Serindere et al (7) reported that RF depth was statistically significantly higher in women. In our study and other studies (1,8,11), no significant difference was found in RF depth according to gender.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Serindere et al (7) reported that RF depth was statistically significantly higher in women. In our study and other studies (1,8,11), no significant difference was found in RF depth according to gender.…”
Section: Discussionmentioning
confidence: 96%
“…In the literature, the anatomical structures of the posterior wall of the nasopharynx were examined using computed tomography (CT) (2,(11)(12)(13) and CBCT (1,(7)(8)(9). CBCT provides accurate and reliable measurements of bone tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations